Utilization of Natural Dyes Solutions and Glycerol for the Quality and Durability of Direct Wet Mount Preparations Storage in Educational Laboratories - Iswiyanti Novita; Linda Yuliana (Tropical Health and Medical Research, 2022)
Educational laboratories require the availability of direct wet mount preparations that can last a long time with good quality. Various studies have mentioned techniques so that preparations can last a long time. This study aims to analyze the composition of dyes and glycerol in wet preparations of worm eggs on the quality and shelf life of the preparations. The solvent variations used for the wet preparations were Angkak 2%, and eosin 2%, with the addition of variations in the concentration of glycerol 20%-45%. The number of treatments and repetitions in the study was 70 samples, which were observed in the first, second, third, and fourth weeks. Based on the ANOVA test, the results showed a significant effect on the parameters measured, namely the type of dye, the type of slide, and the shelf life of the preparation (storage) in natural dye solution (2% ethanol extract of Angkak solution) and synthetic dye solution (2% eosin solution). The correlation test results of storage time treatment on the clarity of the preparations showed that the longer the storage, the lower the clarity of the preparations (r=-0.46246). The correlation test results of storage time treatment on the contrast of the preparations showed that the longer the storage, the less the contrast was not so strong (r=-0.26375). The correlation test results of storage time treatment on the quality of the preparations showed that the longer the storage, the lower the quality of the preparations (r=-0.51346). The conclusion is that the best quality of wet preparations is preparations that are stored for four weeks using a flat object-glass with a mixture of 1:1 dye solution of 2%-glycerol solution of 35% and 1:1 mixture of a 2%-glycerol solution of 1:1 solution. Further research is needed on the concentration of the dye solution mixture to find the best formulation for improving the quality and resistance of wet preparations.